Comparison of Objective Measures for Predicting Perceptual Balance and Visual Aesthetic Preference - Hübner, Ronald; Fillinger, Martin G. (Frontiers in Psychology, 2016)
The aesthetic appreciation of a picture largely depends on the perceptual balance of its elements. The underlying mental mechanisms of this relation, however, are still poorly understood. For investigating these mechanisms, objective measures of balance have been constructed, such as the APB (Assessment of Preference for Balance) score of Wilson and Chatterjee (2005). In the present study we examined the APB measure and compared it to an alternative measure (DCM; Deviation of the Center of ‘Mass’) that represents the center of perceptual ‘mass’ in a picture and its deviation from the geometric center. Additionally, we applied measures of homogeneity and of mirror symmetry. In a first experiment participants had to rate the balance and symmetry of simple pictures, whereas in a second experiment different participants rated their preference (liking) for these pictures. In a third experiment participants rated the balance as well as the preference of new pictures. Altogether, the results show that DCM scores accounted better for balance ratings than APB scores, whereas the opposite held with respect to preference. Detailed analyses revealed that these results were due to the fact that aesthetic preference does not only depend on balance but also on homogeneity, and that the APB measure takes this feature into account.